Type material of Arctiinae (Lepidoptera: Erebidae) in the collection of the Museo Argentino de Ciencias Naturales Bernardino Rivadavia (Buenos Aires, Argentina) - Rodriguez-Ramirez, Joanna; Beccacece, Hernan Mario; Pinheiro, Lívia Rodrigues; Grados, Juan; Morono-Brizuela, Maria Lucila (Zootaxa, 2020)
The Museo Argentino de Ciencias Naturales Bernardino Rivadavia (MACN) possesses one of the most important Lepidoptera collections in South America. Here are deposited several type specimens of Lepidoptera, particularly of Arctiinae, described by Burmeister, Berg, Snellen, Jörgensen, Giacomelli, Orfila, and Forster. This study presents a catalogue with complete information and photographs of most type specimens of Arctiinae housed in the MACN. Additionally, we provide comments on the type material presumably deposited in MACN but not found by the authors. A total of seven lectotypes are designated and a new synonymy is proposed: Eurota (sic) julia Orfila, 1931 is a junior synonym of Eurata hermione Burmeister, 1878.